Evaluation of Cassava Germplasm Accessions for High Tuber Yield and Starch Content for Industrial Exploitations - Velmurugan, M; Manickam, S.; Pugalendhi, L. (JOURNAL OF ROOT CROPS, 2017)
A total of 368 cassava germplasm accessions are being maintained at Tapioca and Castor Research Station, Yethapur. The trial on the evaluation of cassava germplasm accessions was laid out in Augmented Block Design (ABD). The accessions are being continuously evaluated for its growth parameters viz., plant height (cm), stem girth (cm), branching habit and yield traits viz., number of tubers, tuber yield plant -1(kg) and quality parameters viz., starch content (%). The experiment was conducted for the peiod from 2012 to 2015 and the results revealed that the plant height ranged from 108.51 cm (Me 519) to 385.41 cm (Me 287) and stem girth ranged from 3.90 cm (Me 75) to 16.4 cm (Me 724 and Me 725). The cassava accessions such as Me 50, Me 224, Me 460, Me 383, Me 866, Me 867, Me 868, Me 869 showed non-branching habit. The maximum (19.10) and minimum number of tubers (2.80) was recorded in Me 866 and Me 616, Me 656 respectively. Yield plant -1 ranged from 1.39 kg (Me 398) to 10.22 kg (Me 155). The lowest (13.00 %) and the highest starch content (30.40%) was recorded in Me 852 and Me 310 respectively. Among the accessions evaluated, Me 681 has excelled with high tuber yield plant -1 (7.53 kg) and starch content (29.33%) when compared to the local check YTP-1 (Me 833) with the tuber yield of 6.27 kg plant -1 and starch content of 26.70%.